The long march of history: farm wages, population and economic growth, England 1209-1869 - Gregory Clark (University of California, Department of Economics, 2005)
The paper forms three series for English farm workers 1209-1869: nominal day wages, the implied marginal product of a day of farm labour, and the purchasing power of a days' wage in terms of farm workers' consumption. These series suggest that labour productivity in English agriculture was already high in the middle ages. Further they fit well with one method of estimating medieval population which suggests a peak English population circa 1300 of nearly 6 million. Finally they imply that both agricultural technology and the general efficiency of the economy was static from 1250 till 1600. Economic changes were in these years entirely a product of demographic shifts. Finally in 1600 to 1800 technological advance in agriculture provided an alternative source of dynamism in the English economy.
Keywords: 330